The effects of combined exercise training on body composition among overweight adults / Tham Yin Choong ... [et al.] - Tham, Yin Choong; Ismail, Ahmad Dzulkarnain; Tan, Chee Hian; Ong, Tah Fatt; Mohd Khairi, Harris (Faculty of Sports Science and Recreation, 2024)
People who have overweight and obese are at increased risk for several serious diseases and health complications. Evidence suggests that exercise training improves overweight and obesity risk factors. However, it is unclear whether health benefits are limited to aerobic or resistance training or whether a combination is more effective in improving the overweight and obese. This study aimed to investigate the effects of combined aerobic and resistance training on body mass index (BMI) and waist-hip ratio (WHR) among overweight adults. This study used the true experimental design with the randomized pretest-posttest control group design. A total of 17 overweight participants took part in this study and were randomly assigned to the control and experimental groups. The experimental group performed eight weeks of aerobic and resistance combination training programs that consisted of 15-minute aerobic and 15-minute resistance exercises for each training session. The BMI and WHR data were obtained before and after the eight weeks of the training program. The paired t-test was used to analyse the pre and post-test data within-group. The combined exercise training significantly decreased the BMI in the experimental group (p = 0.001). However, there was no difference in the BMI in the control group. There was no significant improvement in the WHR for the experimental and control groups. The combined exercise training gave more benefits for weight loss. Therefore, programs designed to reduce overweight or obesity rates should encourage the practice of combined exercise training. In this study, eight weeks of combined exercise training was effective in reducing BMI but not in WHR among overweight adults.